2023
DOI: 10.26773/mjssm.230302
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in Shot Distribution and Accuracy in International 3x3 Basketball Tournaments

Abstract: This study aimed to (a) investigate shot distribution and accuracy in international 3x3 basketball tournaments by classifying shot attempts into three types (two-point, mid-range, and paint shots) and (b) compare them among age and sex categories (senior men, senior women, under-18 men, and under-18 women). Ninety-one games from the FIBA 3x3 World Cup 2019 and the FIBA 3x3 Under-18 World Cup 2019 were analyzed using a notational analysis method. The Mann-Whitney U test with Benjamini-Hochberg correction was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…On the other hand, after analysing the results in an individual perspective, the total number of throws and two-point throws attempted was not associated with significant differences between the genders. These results are in agreement with previous studies carried out in basketball, where male athletes showed greater efficiency and number of throws taken during competitions [32]. These differences in performance are related to anthropometric, functional and motor differences between male and female teams [33].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, after analysing the results in an individual perspective, the total number of throws and two-point throws attempted was not associated with significant differences between the genders. These results are in agreement with previous studies carried out in basketball, where male athletes showed greater efficiency and number of throws taken during competitions [32]. These differences in performance are related to anthropometric, functional and motor differences between male and female teams [33].…”
Section: Discussionsupporting
confidence: 93%
“…Their list coincides with the data of methodological recommendations on training 3x3 players [19,20,21]. Later, game situations were used, which required tactical interaction of 2 or 3 players in 3x3; it corresponds to modern trends and the latest publications on game tactics [6,9,24]. Special attention is paid to tactical interactions in the attack in 3x3 basketball, basing on the use of different types of screens, because a number of studies have proved the quantitative advantage of these interactions in the game of the world's leading teams and the feasibility of screens use in 3x3 basketball [25].…”
Section: Discussionmentioning
confidence: 94%
“…Overall, the implemented developed program had a positive effect on the competitive performance of the experimental group, which demonstrated significant improvement in several key areas. However, this team still has some room for improvement, as their overall performance is still below the world requirements for players of this age [6,7,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation